Experimental and numerical investigation on melting of phase change material in a disc-shaped container via hot air jet impinging - Kiyak, Burak; Öztop, Hakan Fehmi; Aksoy, I. Gokhan (Pergamon-Elsevier Science Ltd, 2024)
Experimental and numerical analyses were performed to investigate the control parameters of a Phase Change Material (PCM) melting by impinging a hot air jet. A novel container was designed to store PCM. The RT25HC was chosen as the PCM, with a 22-26 degrees C melting temperature. Experiments were conducted under a constant air temperature (Tair) of 40 degrees C with two different Reynolds (Re) numbers, 2235 and 4470. The analysis was performed for three jet length-to-container diameter ratios (H/D): 0.4, 0.5, and 0.6. The Finite Volume Method (FVM) was used to solve three-dimensional and time-dependent governing equations. It was found that the optimum melting time was attained when the H/D = 0.5. The measurements, thermal camera images and the numerical results displayed good agreement. The influence of H/D on the melting time decreases as the Reynolds number increases, decreasing the difference between the maximum and minimum melting rates from 23.05 % at Re = 2235 to 7.67 % at Re = 4470. In the experimental comparison, when considering H/D = 0.5, which corresponds to the case with the maximum stored energy at both Reynolds numbers, the energy stored by the H/ D = 0.6 cases is 26.4 % lower at Re = 2235. In contrast, this difference reduces to 5.03 % at Re = 4470.
Keywords: Phase change material; Energy storage; Hot air jet; Container design; Thermal energy storage